Atomic‐Layer‐Confined Doping for Atomic‐Level Insights into Visible‐Light Water Splitting1. Issue 32 (25th June 2015) - Lei, Fengcai; Zhang, Lei; Sun, Yongfu; Liang, Liang; Liu, Katong; Xu, Jiaqi; Zhang, Qun; Pan, Bicai; Luo, Yi; Xie, Yi
Abstract A model of doping confined in atomic layers is proposed for atomic‐level insights into the effect of doping on photocatalysis. Co doping confined in three atomic layers of In2S3 was implemented with a lamellar hybrid intermediate strategy. Density functional calculations reveal that the introduction of Co ions brings about several new energy levels and increased density of states at the conduction band minimum, leading to sharply increased visible‐light absorption and three times higher carrier concentration. Ultrafast transient absorption spectroscopy reveals that the electron transfer time of about 1.6 ps from the valence band to newly formed localized states is due to Co doping. The 25‐fold increase in average recovery lifetime is believed to be responsible for the increased of electron–hole separation. The synthesized Co‐doped In2S3 (three atomic layers) yield a photocurrent of 1.17 mA cm−2 at 1.5 V vs. RHE, nearly 10 and 17 times higher than that of the perfect In2S3 (three atomic layers) and the bulk counterpart, respectively.